Factors Influencing Open-air Defecation in Tribal Villages of Dhamni and Dhodani in Raigad District of Maharashtra: A Cross-sectional Study - Ashlesha Tawde; Noopur Kulkarni (Wolters Kluwer Medknow Publications, 2024)
Background and Objectives: The burden of poor sanitation, particularly in India, is exacerbated by challenges in infrastructure and education. Previous studies reveal unsatisfactory sanitary conditions, the association between low standard of living and open defecation, the need for collective effort, the positive impact of improved sanitation on child height, and factors hindering latrine adoption. This study aimed to identify factors influencing open-air defecation in tribal villages of Dhamni and Dhodani in the Raigad district of Maharashtra, India. Subjects and Methods: Data were collected through a door-to-door survey using a pretested questionnaire from December 2019 to February 2020, covering sociodemographic information, personal and family history, and environmental factors. Out of 130 willing participants, 112 were included in the final analysis. Descriptive statistics, including percentages, means, and standard deviations, were used to analyze the data. The Chi-square test was used to compare categorical variables. Results: The study found that a significant majority of the subjects (75%) engaged in open field defecation (OFD), whereas a smaller proportion used household latrines (25%). Among those practicing OFD, a considerable portion (46%) defecated in agricultural fields, and a notable percentage (27%) preferred defecating near water sources. Conclusion: The study revealed unsatisfactory sanitary conditions in the research area. It was observed that rural areas with higher levels of literacy exhibited a lower prevalence of OFD and higher rates of sanitary latrine utilization.